Ultrasound-Guided Nerve Hydrodissection With 5% Dextrose 4 Weeks After Steroid Injection in Treatment of Carpal Tunnel Syndrome: A Retrospective Study - He, Juan-juan; Wei, Xiao-mei; Dou, Zu-lin; Zhang, Jiang-shan; Wei, Zhen-hai; Zhang, Wei-xi; Jiang, Li (Frontiers in Neurology, 2022)
Objective: To investigate the efficacy and safety of ultrasound-guided nerve hydrodissection (HD) with 5% dextrose (D5W) as add-on therapy after corticosteroid injection in carpal tunnel syndrome (CTS), and provide a novel strategy. Methods: In this retrospective study, patients with CTS who received ultrasound-guided nerve HD with D5W as add-on therapy after corticosteroid injection (combination group) were enrolled. Patients received corticosteroid injection without add-on therapy (steroid group) was recruited as control group. Ultrasound-guided nerve HD with D5W was performed 4 weeks after corticosteroid injection. Treatment effectiveness were assessed by visual analog scale (VAS) and Boston Carpal Tunnel Syndrome Questionnaire (BCTQ). The assessment was performed at baseline and 4, 8, and 12 weeks after corticosteroid injection. In addition, adverse events were recorded in this study. Results: 49 patients and 62 wrists meeting the criteria were included, with 24 patients and 31 wrists in steroid group, 26 patients and 31 wrists in combination group. Compared with baseline data, both groups showed greater improvement in VAS, BCTQs (BCTQ severity) and BCTQf (BCTQ function) at 4 weeks, 8 weeks and 12 weeks follow-up. VAS, BCTQs and BCTQf scores at baseline and week 4 were comparable between steroid group and combination group. Compared with steroid group, combination group exhibited a significant reduction in VAS, BCTQs and BCTQf at 8-week and 12-week follow-up (P<0.01). No adverse event occurred in any group. Conclusions: Our results showed that ultrasound-guided nerve HD with D5W as add-on therapy after corticosteroid injection was efficacious and safe in CTS, and combination therapy is more beneficial than corticosteroid monotherapy in the improvement of symptoms and function at 8-week and 12-week follow-up.